Statistics and data analysis for nursing research - Polit, Denise F. (Pearson, 2010)
This edition uses a conversational style to teach students how to use statistical methods and procedures to analyze research findings. Readers are guided through the complete analysis process from performing a statistical analysis to the rationale behind doing so